Profil Pemecahan Masalah Siswa Auditorial Kelas X Slta pada Materi Sistem Persamaan Linear Dua Variabel - Mubarik, Mubarik (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
This research to get the description of profile problerm solving auditorial student of class X senior high school at items LESTV. This research used is qualitative method by using descriptive approach qualitative which is by a problem solving Polya phase. The result of research showed that the profile of student auditorial in solved the problem is tend to use thekinesthetic student characteristic and visual student characteristic.